A New Marketing Paradigm-Social Media or Web 2.0: An Empirical Analysis to Study the Awareness, Key Deliverables, Engagement and Usage of Social Media by Small and Medium Enterprises in Delhi - Sharma, Monika (Indian Journal of Marketing, 2012)
The new wave of social media marketing mainly done through social media/Web 2.0 tools like Blogs, Wikis, RSS, Social Networks, Forums/Communities is no longer limited to only large organizations, but is also gaining hold in Small and Medium Enterprises in India. Capturing the voice of the customer has significantly become important as he has more power than ever. Consumers tweet, blog, share, use Facebook or some other forum to dissect every detail of what brands claim and promise in marketing - right from product performance to customer service. The key deliverables that social media promises to provide is not just restricted to large organizations but also to SMEs in creation of brand awareness, developing initial level of trust in the organizations, generation of sales, engaging customers in interactions, and influencing customer purchase decision in a major way. This paper attempts to study the awareness, understanding levels of different social media tools in present times among small and medium enterprises in Delhi and determining the key deliverables of social media to SMEs and the various activities these organizations are engaged with, using various social media tools like Blogs, Social Networks like Facebook, Micro blogging sites like Twitter and professional networks like Linkedln.